Meta-analysis of Effect of Otago Exercise Program on Stroke Patients - Ziwen PEI; Mian WANG; Xianmei MENG (康复学报)
Objective:To evaluate the effect of Otago exercise program on the patients with stroke.Methods:Randomized controlled trials(RCTs)about Otago exercise program for falls efficacy balance function in patients with stroke were electronically searched in PubMed, Cochrane Library, Web of Science, EMbase, CNKI Chinese Journal Full-text Database, Wanfang Database, VIP Database and Chinese Biomedical Literature Database from the establishment of each database to May, 2018.All data were analyzed with RevMan 5.3 software.Results:A total of seven studies that represented 545 participants were evaluated. Meta-analysis showed that Otago exercise program had positive effects on improving patients'falls efficacy [SMD=1.10, 95%CI(0.75, 1.45), P<0.01] and Berg Balance Scale(BBS)scores [MD=5.55, 95%CI(4.15, 6.96), P<0.01].It could also improve Modified Barthel Index(MBI) [MD=8.10, 95%CI(1.56, 14.64), P=0.02] and European Quality of Life-5 Dimensions scores(EQ-5D) [MD=0.13, 95%CI(0.05, 0.20), P=0.002]. However, no statistically significant difference was found on Timed Up and Go Test(TUGT) [MD=-3.39, 95%CI(-7.09, 0.31), P=0.07].Conclusion:Otago exercise program is effective to improve falls efficacy, balance function, daily activities and quality of life of patients with stroke. Due to the limited quantity and quality of included studies, the above conclusion needs to be verified by more high-quality research.